2010
DOI: 10.1002/qua.22805
|View full text |Cite
|
Sign up to set email alerts
|

The quantum theory of atoms in positronic molecules: A case study on diatomic species

Abstract: This article presents the first systematic study of a series of diatomic positronic species using the recently proposed regional approach: the quantum theory of atoms in positronic molecules (QTAIPM). This survey includes the LiH,e þ , NaH,e þ , LiF,e þ , NaF,e þ , BeO,e þ , MgO,e þ , CN À ,e þ , and OH À ,e þ species as typical examples. The computational algorithm of the whole analysis is communicated and reviewed in detail. The topological analysis of the joint density distribution reveals topological struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 95 publications
(78 reference statements)
3
52
0
Order By: Relevance
“…[62] In all the considered species the positron retains in the basin of the most electronegative atom except from the case of cyanide anion, CN À , where the positron's population was almost evenly distributed in both atomic basins. [62] In present analysis we employ the MC-QTAIM trying to reveal the detailed nature of the AIM structure as well as the bonding mode of [H À , e + , H À ]. Let us first very briefly discuss the energetics and stability of [H À , e + , H À ] where CVR considered this species at various multicomponent ab initio levels.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…[62] In all the considered species the positron retains in the basin of the most electronegative atom except from the case of cyanide anion, CN À , where the positron's population was almost evenly distributed in both atomic basins. [62] In present analysis we employ the MC-QTAIM trying to reveal the detailed nature of the AIM structure as well as the bonding mode of [H À , e + , H À ]. Let us first very briefly discuss the energetics and stability of [H À , e + , H À ] where CVR considered this species at various multicomponent ab initio levels.…”
Section: Resultsmentioning
confidence: 94%
“…Particularly, the previous MC‐QTAIM analysis of the positronic species revealed that the positron is not capable of accumulating enough electrons around itself to form an independent atomic basin . In all the considered species the positron retains in the basin of the most electronegative atom except from the case of cyanide anion, CN − , where the positron's population was almost evenly distributed in both atomic basins . In present analysis we employ the MC‐QTAIM trying to reveal the detailed nature of the AIM structure as well as the bonding mode of [ H − , e + , H − ].…”
Section: Resultsmentioning
confidence: 99%
“…[54][55][56] To deal with certain types of non-BO wavefunctions, like the NEO wavefunctions, an extended version of the QTAIM, termed the multi-component QTAIM (MC-QTAIM), has been recently introduced. [57][58][59][60][61][62][63][64][65][66][67][68][69] The MC-QTAIM methodology hasb een applied to molecules containing hydrogen isotopes as quantum waves, [60,67] as well as to positronic, [57][58][59] and muonic species. [66,68,69] In the present study,t he MC-QTAIM analysisi su sed to deciphert he AIM structure of m + -substituted malonaldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this supposition, positron, the anti-particle of electron, does not deserved to be placed in the PT since previous computational studies revealed that this particle is unable to form independent AIM. 39,[45][46][47] On the other hand, the muonic Helium as a combined exotic particle, composed of an alpha particle and an encircling   , deserves to be placed in the same box of hydrogen in the PT since it forms its own AIM quite similar to proton containing atomic basins. 30 The short life time of the muonic Helium composite is not an obstacle since many radioactive and superheavy nuclei, composed of protons and neutrons, may have also exceedingly short lives but still to be placed in the PT.…”
Section: Introductionmentioning
confidence: 99%